2-(Anthracenyl)-4, 5-bis(2, 5-dimethyl(3-thienyl))-1H-imidazole: regulatable stacking structures, reversible grinding- and heating-induced emission switching, and solid-state photodimerization behavior. Issue 1 (21st October 2015) - Chen, Jun-Feng; Gong, Dan-Ping; Wen, Jing; Ma, Haibo; Cao, Deng-Ke
Abstract : The molecular assembly of anbdtiH leads to three distinct solid-state structures: anbdtiH·CH3 Cl (1 ), anbdtiH·2CH3 OH (2 ) and anbdtiH2 ·CF3 COO·CH3 OH·H2 O (3 ), which have orange-red, blue and green emissions, respectively. Abstract : 2-(Anthracenyl)-4, 5-bis(2, 5-dimethyl(3-thienyl))-1 H -imidazole (anbdtiH) has been synthesized. Its three solid-state structures, anbdtiH·CH3 Cl (1 ), anbdtiH·2CH3 OH (2 ) and anbdtiH2 ·CF3 COO·CH3 OH·H2 O (3 ), have been constructed by skillfully choosing CHCl3 or CH3 OH as the solvent and using or not using CF3 COOH, with the aim of modifying the intermolecular hydrogen bonds and/or π⋯π stacking interactions. The three distinct structures show significantly different solid-state luminescence behaviors, an orange-red emission at 603 nm for1, a blue emission at 453 nm for2, and a green emission at 533 nm for3 . Upon grinding, these emission wavelengths exhibit evident variations, a blue-shift of Δ λ = 83 nm for1, a red-shift of Δ λ = 20 nm for2, and a blue-shift of Δ λ = 54 nm for3 . The emission color of1 can be reversibly switched between orange-red and green upon regulation of the intermolecular (N–H)imidazole ⋯Nimidazole hydrogen bonds by a grinding–heating process. Moreover, compound3 can undergo a solid-state [4π + 4π] photodimerization reaction upon irradiation with sunlight, forming3-dimer . Based on the crystal structures of1–3, this work discusses the relationship between the molecular stacking mode and the luminescence behavior/photochemical reactivity.